SKILLS FOR CREATING SUPPORTIVE LEARNING ENVIRONMENTS – AN ESSENTIAL COMPONENT OF TEACHERS`PROFESSIONAL COMPETENCE - Kiilu, Kristi; Läänemets, Urve; Kalamees-Ruubel, Katrin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The current research on music teachers’ professional skills of structuring and developing supportive learning environments for implementation of National Curricula is the third in line, based on a pilot project of 2013, a study of 2015. The research problem for all the three studies was “How do music teachers at general comprehensive schools comprehend supportive learning environment and opportunities for their design and development. The data collected and analysed (n=70) in 2019 allow to follow the development of teachers’ professional abilities and creativity at structuring and designing supportive environments for learning music at general comprehensive schools and kindergartens. If smartly designed and created, they promote learning, lead to higher academic achievement and contribute to students’ self-esteem. The study has also provided information about teachers’ professional approaches, real environments at schools and the needs for improvement. The analysis of the data, providing some insights allows to make recommendations for teacher training, for curriculum design at school level and offer suggestions for cultural activities in local communities supporting cohesion and identity building in society. Current turbulent times require increasingly wider competences and creativity from teachers for making music education socially meaningful.